Elasto-Plastic Contact of Rough Surfaces - Willner, Kai (Computational Methods in Contact Mechanics III, 1997)
If two rough surfaces are brought into contact, asperities will deform either elastically or plastically. While the mode of initial deformation will depend on geometrical and material properties at any single asperity, the deformation upon unloading and reloading will be in the elastic regime. As it is not feasible to model the behaviour of each single asperity in a structural mechanics application, global contact laws are needed. In the present paper such contact laws are derived for several deformation models.
UnivIS-Import:2015-04-16:Pub.1997.tech.FT.FT-TM.elasto